(untitled) (Bangladesh Journal of Botany, 2021)
The sole and sequential application of herbicide and straw mulch on weed growth and productivity of rainfed direct seeded rice, were studied with 12 treatments during kharif 2019. Results showed that the application of oxadiargyl fb rice straw mulch @ 6 t/ha registered significantly the lowest weed density and dry weight at 60 DAS; however, it was statistically at par with oxadiargyl fb hand weeding. Weed free check produced the highest grain yield (3.05 t/ha) which was at par with the sequential application of oxadiargyl fb rice straw mulch @ 6 t/ha (2.99 t/ha) and oxadiargyl fb rice hand weeding (2.90 t/ha). Application of oxadiargyl fb rice straw mulch @ 6 t/ha fetched the maximum net return of Rs. 17528/- per ha and return per rupee invested of 1.52. Application of oxadiargyl fb rice straw mulch @ 6 t/ha could be recommended for managing complex weed flora, higher productivity and greater profit in rainfed direct seeded rice cultivation. Bangladesh J. Bot. 50(3): 671-677, 2021 (September)